NOTCH and DNA repair pathways are more frequently targeted by genomic alterations in inflammatory than in non‐inflammatory breast cancers. Issue 3 (5th February 2020) - Bertucci, François; Rypens, Charlotte; Finetti, Pascal; Guille, Arnaud; Adélaïde, José; Monneur, Audrey; Carbuccia, Nadine; Garnier, Séverine; Dirix, Piet; Gonçalves, Anthony; Vermeulen, Peter; Debeb, Bisrat G.; et al.
Abstract : Inflammatory breast cancer (IBC) is the most pro‐metastatic form of breast cancer. Better understanding of its pathophysiology and identification of actionable genetic alterations (AGAs) are crucial to improve systemic treatment. We aimed to define the DNA profiles of IBC vs noninflammatory breast cancer (non‐IBC) clinical samples in terms of copy number alterations (CNAs), mutations, and AGAs. We applied targeted next‐generation sequencing (tNGS) and array‐comparative genomic hybridization (aCGH) to 57 IBC and 50 non‐IBC samples and pooled these data with four public datasets profiled using NGS and aCGH, leading to a total of 101 IBC and 2351 non‐IBC untreated primary tumors. The respective percentages of each molecular subtype [hormone receptor‐positive (HR+)/HER2−, HER2+, and triple‐negative] were 68%, 15%, and 17% in non‐IBC vs 25%, 35%, and 40% in IBC. The comparisons were adjusted for both the molecular subtypes and the American Joint Committee on Cancer (AJCC) stage. The 10 most frequently altered genes in IBCs were TP53 (63%), HER2/ERBB2 (30%), MYC (27%), PIK3CA (21%), BRCA2 (14%), CCND1 (13%), GATA3 (13%), NOTCH1 (12%), FGFR1 (11%), and ARID1A (10%). The tumor mutational burden was higher in IBC than in non‐IBC. We identified 96 genes with an alteration frequency ( p < 5% and q < 20%) different between IBC and non‐IBC, independently from the molecular subtypes and AJCC stage; 95 were more frequently altered in IBC, including TP53, genes involved in the DNA repair ( BRCA2 ) and NOTCH pathways, and one ( PIK3CA ) was more frequently altered in non‐IBC. Ninety‐seven percent of IBCs displayed at least one AGA. This percentage was higher than in non‐IBC (87%), notably for drugs targeting DNA repair, NOTCH signaling, and CDK4/6, whose pathways were more frequently altered (DNA repair) or activated (NOTCH and CDK4/6) in IBC than in non‐IBC. The genomic landscape of IBC is different from that of non‐IBC. Enriched AGAs in IBC may explain its aggressiveness and provide clinically relevant targets. Abstract : We compared the DNA mutational and copy number profiles and mRNA expression profiles of a large series of IBC and noninflammatory breast cancer (non‐IBC) untreated primary tumors. Compared to non‐IBC samples, IBC samples displayed more frequent alterations in the NOTCH and DNA repair pathways independently form the unbalance in term of molecular subtypes and American Joint Committee on Cancer stages.